Generalized Anxiety Disorder Level Among Employees and Students after Conflicts in Duhok City - Arezi, Musaab (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
This study aimed to determine the level of Generalized Anxiety Disorder (GAD) among residents in Duhok City, after a series of trauma and conflicts, examine gender differences in GAD levels, and assess variations across different job categories and age groups. A descriptive, analytical cross-sectional design was employed using the DSM-5 Severity Measure for Generalized Anxiety Disorder – Adult. The study utilized simple random sampling to recruit 1,430 participants from various locations in Duhok city. The data were processed through descriptive statistics, one-sample t-test, independent samples t-test, and one-way ANOVA. Results showed a high prevalence of GAD among the population by (24.6% mild, 12.2% moderate, and 3.3% sever), with females experiencing significant higher (52.1%) compared to male by (27.8%). There were also significant variations across occupational groups, and the highest anxiety level was seen amongst the non-governmental employees, followed by government employees and students. Variations by age showed that the anxiety levels were higher amongst the older age group compared to the younger age groups. These results are helpful for planning specially targeted mental health intervention and policy in the region.